IMPLEMENTASI REGULASI JAMINAN PERSALINAN DI KABUPATEN SLEMAN (Kajian Pada Bidan PraktikYang Melakukan Perjanjian Kerja Sama ) - , Achmad Arifurrohman; , drg. Suryono, S.H.,Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: The high maternal mortality rate (MMR) in Indonesia that is 228 per 100,000 live births to encourage governments to make policies that Maternity Insurance program is an expansion of the Community Health Insurance as well as to accelerate the achievement of the MDGs targets by 2015. Delivery by health workers has contributed to the decline in maternal mortality rate of 45%. Midwives are health professionals who practice the lead in aid delivery to the public. Objectives: To determine compliance with the regulations implementing Maternity Insurance in District Sleman especially in midwifery practice doing Cooperation Agreement (MCC) and the constraints that arise when implementing. Methods: This study uses a description of the normative and the sociological approach. Primary data was collected from questionnaires distributed to respondents. Secondary data obtained from Maternity Insurance activity of the District Health Office in Sleman. Of the total population of midwives practice only 34 people 52 people who met the inclusion criteria of respondents. The results: Of the aspects of patient participation Maternity Insurance, portability Maternity Insurance, authority midwifery practice, Maternity Insurance service tariffs, the right of patients to follow the family planning program, Maternity Insurance costs sharing for patients, the provision of administration for patients Maternity Insurance sheet, when filing a claim is in conformity with the regulations. Provision of contraceptives by the BKKBN is not in accordance with the regulations. There is no constraint of the socialization aspect Maternity Insurance program, the participation of midwives in the program Maternity Insurance, the disbursement of claims, the administrative process of making the agreement and the need for continued cooperation Maternity Insurance program. Constraints contained in the referral of patients to higher health facilities. Conclusion: The implementation of the program is in conformity with the regulations Maternity Insurance except on aspects of the provision of contraceptives. While the obstacles that arise when the implementation is the difficulty in referring patients to higher health facilities Maternity Insurance.